2013
DOI: 10.1007/s00198-013-2424-4
|View full text |Cite
|
Sign up to set email alerts
|

Implications of local osteoporosis on the efficacy of anti-resorptive drug treatment: a 3-year follow-up finite element study in risedronate-treated women

Abstract: Subjects in the inadequate drug response group exhibited high local BR at the supero-anterior and supero-posterior regions. These high local BR values coincided with FE-predicted critical strain regions, whereas subjects from the adequate drug response group showed significantly reduced strain regions. The superiority of coupling geometry (BR) with structure (F cr) over bone mineral density measurements alone by monitoring local osteoporosis has been illustrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Hence, understanding the decline in BMD due to MM-induced osteoporosis may be unreliable. Second, BMD has been challenged as a limited tool for the diagnosis of osteoporosis itself as it only partially predicts fracture risk, [18] which renders its use in the diagnostic evaluation of MM less valid. Also, routine assessment of BMD in MM patients has not been recommended due to methodological difficulties of this technique in these patients and the frequent use of bisphosphonates in all symptomatic MM patients.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, understanding the decline in BMD due to MM-induced osteoporosis may be unreliable. Second, BMD has been challenged as a limited tool for the diagnosis of osteoporosis itself as it only partially predicts fracture risk, [18] which renders its use in the diagnostic evaluation of MM less valid. Also, routine assessment of BMD in MM patients has not been recommended due to methodological difficulties of this technique in these patients and the frequent use of bisphosphonates in all symptomatic MM patients.…”
Section: Introductionmentioning
confidence: 99%
“…trabecular-level changes, which may produce different results. However, the accuracy and reliability of FE-predicted bone strength have been demonstrated in several studies162945. Also, this study only considered CT dose reduction via the variation of tube current but dose can also be reduced by reducing tube voltage or increasing pitch38 for instance.…”
Section: Discussionmentioning
confidence: 98%
“…Finite-element (FE) modeling has increasingly been used to perform structural analysis of bones to assess strength and understand the mechanism underlying bone fracture1516. FE analysis acts as a non-invasive alternative to assess bone strength in-vivo , where radiological scan data of patients are translated into patient-specific three-dimensional (3D) anatomical models.…”
mentioning
confidence: 99%
“…Indeed, recent studies have demonstrated that reductions in the QCT-assessed BR are well correlated with improvements in the CSMI, CSA, and BMD. 30,31) Despite these limitations, our study has clearly demonstrated the longterm therapeutic efficacy of risedronate. DXA with AHA may ensure easy and accurate measurement of the BMD and bone geometry in terms of bone quality in clinical practice, both of which reflect bone strength.…”
Section: Discussionmentioning
confidence: 81%